Successful angioplasties using high pressure large balloons in a patient with severe anastomotic pulmonary artery stenosis soon after single-lung transplantation. Issue 1 (July 2020) - Shiraga, Kazuhiro; Hirata, Yoichiro; Saito, Akihito; Ozcelik, Nazire; Asakai, Hiroko; Inuzuka, Ryo; Soma, Katsura; Sato, Masaaki; Hirata, Yasutaka; Oka, Akira
Abstract: A 59-year-old man received a single-lung transplantation due to interstitial pneumonitis. Severe anastomotic pulmonary artery stenosis (PAS) resulting in hypoxia and respiratory symptoms was found in the immediate postoperative period. A scintigraphy showed severe hypoperfusion of the left transplanted lung with 7% of the total pulmonary blood flow. On postoperative days (POD) 29 and 64, the patient underwent serial balloon angioplasties without any complications. Based on the balloon selection criteria for PAS after heart surgery in children, a high-pressure large balloon was used with resultant improvement in respiratory signs and symptoms without any complications. The patient was discharged on POD 92. A follow-up scintigraphy on POD 169 revealed 58% of blood distribution to the left lung. The patient has been doing clinically well and remained asymptomatic one year after the transplantation. Balloon angioplasty with a high-pressure large balloon without stent implantation during an early postoperative period may be a safe and effective strategy. The balloon selecting criteria used in pediatric patients may be applied in the adult lung transplant recipients. <Learning objective: Anastomotic pulmonary artery stenosis (PAS) in a single-lung transplant recipient is a critical complication. A balloon angioplasty with a high-pressure large balloon should be a first choice for anastomotic PAS, because it is safer than stent implantation especially for transplant recipients. And the balloon selecting criteria used in children with congenital heart disease may be applied in the adult lung transplant recipients.>